PREPARASI DAN PENENTUAN JENIS OKSIDA BESI PADA MATERIAL MAGNETIK PASIR BESI LANSILOWO - Ricka Prasdiantika; Susanto Susanto (Universitas Gadjah Mada, 2016)
This study aims to preparation, identify the content, and determine the type of iron oxide on the magnetic material from Iron Sand Lansilowo. Magnetic material is separated from iron sand using an external magnet. Magnetic material washes by using aquadest and dried at 80 °C. Materials were characterized by X-Ray fluorescence (XRF), Fourier Transform Infrared (FT-IR) spectrophotometer, X-ray diffractometer (XRD) and Transmission electron microscope (TEM). The results show that the magnetic material of iron sand Lansilowo contains elements of Fe (46.13%), the element Cr (28.08%), Mg (10,11%), Si (8.20%) and other minor elements. Iron oxide contained in iron sand Lansilowo is dominated by magnetite iron oxide (Fe3O4). The results of characterization show that the magnetic material of iron sand still contain oxide impurities such as silica oxide and chromium oxide